Preparation method of boron nitride aerogel adsorbent for removing heavy metal ions in flue gas based on artificial electron vacancies
A boron nitride aerogel with artificial electron vacancies addresses the challenge of heavy metal removal in high-temperature flue gas by enhancing adsorption capacity and reducing pollution through a synthesis process involving melamine, boric acid, and ZnCl2, effectively capturing metals like cadmium and lead.
Patent Information
- Application Number
- CN202411100525.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2024-12-20
AI Technical Summary
Existing technologies are inadequate for efficiently and cleanly removing heavy metal pollutants from high-temperature flue gas generated by the incineration of solid waste, posing a threat to the environment and human health.
A method for preparing a boron nitride aerogel adsorbent with artificial electron vacancies, involving the synthesis of melamine, boric acid, and ZnCl2, followed by ultrasonication, freeze-drying, and calcination, to create a material with enhanced adsorption capacity for heavy metals in high-temperature flue gas.
The boron nitride aerogel effectively adsorbs heavy metals such as cadmium, lead, and copper, significantly reducing flue gas pollution by increasing adsorption capacity and reducing metal particle formation, even in high-temperature conditions.
Smart Images

Figure CN119158530A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of joint control of multiple air pollutants, and specifically provides a method for preparing a boron nitride aerogel adsorbent for removing heavy metal ions in flue gas based on artificial electron vacancies. Background Art
[0002] Metal pollution has caused serious damage to the environment and posed a serious threat to people's lives and health. Removing heavy metal pollutants from flue gas is still a very serious problem. The "Opinions on Further Strengthening the Prevention and Control of Heavy Metal Pollution" clearly pointed out the need to strengthen the clean production transformation of key industry enterprises. Strengthen the development and application of clean production processes in key industries. There are many sources of heavy metal components in flue gas, a large part of which comes from the incineration of solid waste. How to reasonably, efficiently and cleanly control the heavy metal pollutants generated by the incineration of solid waste has become an important condition for promoting the peaceful and stable development of my country's ecological environment.
[0003] In summary, developing a new adsorbent material that can adsorb heavy metal substances in high-temperature flue gas is an important issue that needs to be solved urgently. Summary of the invention
[0004] In view of this, the present invention provides a method for preparing a boron nitride aerogel adsorbent for removing heavy metal ions in flue gas based on artificial electron vacancies.
[0005] The technical solution provided by the present invention is specifically a method for preparing a boron nitride aerogel adsorbent for removing heavy metal ions in flue gas based on artificial electron vacancies, comprising the following steps:
[0006] Step 1: Weigh melamine C3H6N6, boric acid B2O3, and Zncl2 respectively to prepare an aqueous solution containing melamine C3H6N6, boric acid B2O3, and Zncl2;
[0007] Step 2: Add tert-butyl alcohol (C4H 10 O solution, stir and mix evenly;
[0008] Step 3: ultrasonically treating the mixed solution obtained in step 2, gradually lowering the temperature to room temperature under an ultrasonic environment, and the mixed solution coagulates into floccules;
[0009] Step 4: freeze-drying the floccules to obtain a freeze-dried substance;
[0010] Step 5: calcining the freeze-dried material to obtain the boron nitride aerogel adsorbent.
[0011] Preferably, in step 1, the mass ratio of melamine C3H6N6, boric acid B2O3 and ZnCl2 is one of 1:0.5:0.05, 1:0.5:0.25 and 1:0.5:0.01.
[0012] Preferably, in step 1, when preparing an aqueous solution containing melamine C3H6N6, boric acid B2O3, and ZnCl2, 105 ml of deionized water at an ambient temperature of 20 to 30°C is used, and stirring is performed with a glass rod until the mixture is evenly mixed, and the stirring time is 20±10 min.
[0013] Preferably, in step 2, the mixed solution and tert-butyl alcohol C4H 10 The volume ratio of O solution is 7:3.
[0014] Preferably, in step 2, the mixed solution and tert-butyl alcohol C4H 10 The O solution was mixed under the conditions that the water bath temperature was set at 85°C and the rotation speed was set at 400 rpm. The ultrasonic time in step 3 was 2 h, and the temperature was reduced from 85°C to room temperature 20-30°C.
[0015] Preferably, the freeze-drying time in step 4 is 48 hours.
[0016] Preferably, nitrogen N2 is used as the protective atmosphere during the calcination in step 5, and the gas flow rate is 50 to 300 ml / min.
[0017] Preferably, in step 5, the calcination time is 3 to 5 hours, and the calcination temperature is 1000 to 1300°C.
[0018] In addition, the present invention also provides an application of the boron nitride aerogel adsorbent, wherein the adsorbent is used to adsorb heavy metals and fine particles in high-temperature flue gas.
[0019] The present invention provides a method for preparing a boron nitride aerogel adsorbent for removing heavy metal ions in flue gas based on artificial electron vacancies. The preparation method is simple, and the obtained gel adsorbent can achieve adsorption of heavy metals in high-temperature flue gas. When used, the volatilized heavy metal gas reacts with the boron nitride aerogel adsorbent, and the generated flue gas is significantly reduced. Moreover, as the specific gravity of the adsorbent increases, the formation of heavy metal particles is significantly reduced, proving that the adsorbent plays a role in high-temperature flue gas.
[0020] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0023] Figure 1 The XRD diagram of the boron nitride aerogel adsorbent Bv-BN prepared by the method disclosed in the present invention;
[0024] Figure 2 This is the XRD pattern of the BN aerogel obtained in the preparation method of the present invention without adding zinc chloride;
[0025] Figure 3 A macroscopic SEM image of the Bv-BN aerogel provided by the present invention;
[0026] Figure 4 A microscopic SEM image of the Bv-BN aerogel provided by the present invention;
[0027] Figure 5 This is an EDS image of the Bv-BN aerogel provided by the present invention;
[0028] Figure 6 This is a macroscopic SEM image of the adsorbed Bv-BN aerogel provided by the present invention;
[0029] Figure 7 for Figure 6 A surface scan of the SEM image;
[0030] Figure 8 This is a microscopic SEM image of the Bv-BN aerogel after adsorption provided by the present invention. DETAILED DESCRIPTION
[0031] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are merely examples of methods consistent with some aspects of the present invention as detailed in the appended claims.
[0032] In order to better adsorb heavy metals and fine particles in warm flue gas, this embodiment provides a method for preparing a boron nitride aerogel adsorbent for removing heavy metal ions in flue gas based on artificial electron vacancies, comprising:
[0033] Step 1: Weigh melamine C3H6N6, boric acid B2O3, and Zncl2 respectively to prepare an aqueous solution containing melamine C3H6N6, boric acid B2O3, and Zncl2;
[0034] Specifically, in step 1, the mass ratio of melamine C3H6N6, boric acid B2O3, and ZnCl2 is one of the three ratios of 1:0.5:0.05, 1:0.5:0.25, and 1:0.5:0.01; then add 105 ml of deionized water at an ambient temperature of 20 to 30° C., and stir evenly with a glass rod until mixed, wherein the stirring time is 20±10 min;
[0035] Preferably, the ratio of boric acid B2O3, melamine C3H6N6 and ZnCl2 in step 1 is 1:0.5:0.05 (1.484 g: 1.5136 g: 0.1635 g);
[0036] Step 2: Add tert-butyl alcohol (C4H 10 O solution, stirring and mixing evenly; the volume ratio of the aqueous solution obtained in step 1 to the tert-butanol solution is 7:3, specifically, 45 ml of tert-butanol solution is added to 105 ml of the solution obtained in step 1.
[0037] In step 2, the mixture is stirred and mixed uniformly by stirring in a water bath, wherein the temperature of the water bath is set at 85° C. and the rotation speed is set at 400 rpm;
[0038] Step 3: ultrasonically treating the mixed solution obtained in step 2, gradually lowering the temperature to room temperature under an ultrasonic environment, and the mixed solution coagulates into floccules;
[0039] The ultrasonic time in step 3) is 2 h, and the temperature is reduced from 85°C to room temperature 20-30°C;
[0040] Step 4: freeze-drying the flocs to obtain a freeze-dried substance; the obtained flocs are placed in a freeze dryer and freeze-dried for 48 hours, so that the moisture in the substance is completely removed;
[0041] Step 5: calcine the freeze-dried material to obtain the boron nitride aerogel adsorbent. Use nitrogen as the protective atmosphere at a flow rate of 200 ml / min. Before calcination, ventilate at a flow rate of 200 ml / min for 15 minutes to ensure that there is no other gas in the tube; the calcination time is between 3 and 5 hours, and the calcination temperature is between 1000 and 1300°C. Finally, boron nitride aerogel can be obtained.
[0042] like Figure 1 and 2As shown in FIG. 2 , the modified BN aerogel of the present application and the BN aerogel obtained without adding zinc chloride have two obvious diffraction peaks at 22.62° and 42.58°, which respectively indicate the (0 02) plane and (1 00) plane of h-BN. Figure 2 compared to, Figure 1 The peak intensity of the modified BN aerogel Bv-BN has a significant weakening tendency, indicating the lack of structural order within the framework. This is because the heating stage during the synthesis process leads to the replacement and volatilization of Zn, which results in the generation of defective electron vacancies and hierarchical pores in the BN boron nitride aerogel, resulting in a decrease in the degree of crystallinity.
[0043] Figure 3 , Figure 4 The SEM images of Bv-BN aerogel at different magnifications show that a large number of hollow tubes can be observed, which are presumably formed by the airflow of zinc ions evaporated at a high temperature above 1273K. Figure 5 It can be seen that it is proved that there is no Zn after the adsorbent is synthesized; Figure 6 , Figure 8 The SEM images of the Bv-BN aerogel after adsorption are magnified at different times. It can be clearly seen from the images that the adsorbed heavy metals are attached to the adsorption machine in the form of small dots. Figure 7 for Figure 6 The surface scan of the SEM image shows that a large amount of Zn ions are adsorbed on the adsorption machine, proving that the adsorption is successful.
[0044] The application of the boron nitride aerogel obtained by the above preparation method is specifically as follows: a double-temperature-section tubular furnace is used, the calcination temperature of the first temperature zone is set to 900±50°C, and the calcination temperature of the second temperature zone is set to 300-600±10°C. After setting the program, the first temperature zone is opened first for the heating program, and the second temperature zone is opened for heating after the time is calculated, so that the temperature zones at both ends are heated to the target set temperature at the same time, the weighed heavy metal is placed in a container and pushed into the first temperature zone, and the placed adsorbent (0.1g) is placed in a container and pushed into the second temperature zone, and the adsorption time is controlled by sampling once every 10 minutes.
[0045] Two scrubbing bottles are set at the tail end of the double-temperature section tubular furnace to neutralize the heavy metal flue gas coming out of the second temperature zone. The front scrubbing bottle is a mixture of sodium hydroxide NaOH with a mass percentage of 5% and deionized water, and the rear scrubbing bottle is a mixture of nitric acid HNO3 with a volume percentage of 10% and deionized water. Finally, the neutralized flue gas is discharged to the outside.
[0046] The boron nitride aerogel adsorbent placed in the second temperature zone of the double-temperature tube furnace reacts with volatile heavy metal substances and eventually adsorbs a large amount of heavy metal substances in the flue gas. The unabsorbed flue gas is neutralized by different acid and alkali washing bottles and then discharged into the atmosphere, which also avoids heavy metal pollution to the air.
[0047] The formation of artificial electron vacancies is mainly due to the presence of Zn replacing the B atom in the BN bond during the BN synthesis process, and finally being removed at the calcination temperature of 1373.15K (higher than the boiling point of Zn of 1180.15K), forming a new electron vacancy at the place of the original B atom. The EDS graph shows that there is no Zn element in the formed BN aerogel, proving that Zn has been successfully removed. The newly formed electron vacancies provide more active sites and enhance the adsorption capacity of heavy metals.
[0048] Boron nitride has excellent adsorption properties for heavy metal substances, such as cadmium, lead, copper and iron. Most of the existing ones use boron nitride to adsorb heavy metal substances in liquids. Boron nitride aerogel is a block-like substance with a better morphological structure, which is easier to use than boron nitride powder.
[0049] The present invention is further explained below in conjunction with specific embodiments, but is not intended to limit the protection scope of the present invention.
[0050] Example 1
[0051] A method for preparing a boron nitride aerogel adsorbent for removing heavy metal ions in flue gas based on artificial electron vacancies comprises the following steps:
[0052] (1) First, 1.484 g of melamine C3H6N6, 1.5136 g of boric acid B2O3 and 0.1635 g of ZnCl2 were mixed and stirred uniformly in proportion, and then added into 105 ml of deionized water, and stirred uniformly with a glass rod for 20 min;
[0053] (2) Add 45 ml of tert-butyl alcohol solution C4H 10 O, and then put it into a water bath, set the water bath temperature to 85°C and the speed to 400 rpm;
[0054] (3) Place the solution obtained in (2) into an ultrasonic device at 85°C for 2 h, and cool to room temperature (20±5°C) under ultrasonic conditions;
[0055] (4) The flocs obtained in (3) are placed in a corundum ark and placed in a cold dryer for 48 hours until the water in the flocs is completely dried;
[0056] (5) The completely dried floccules in (4) are placed in a tubular furnace and calcined. During calcination, nitrogen N2 is used as a protective atmosphere at a flow rate of 200 ml / min. Before calcination, the gas is turned on for 15 minutes until the tube is filled with nitrogen N2. The calcination time is set at 4 hours and the calcination temperature is set at 1100°C. Finally, a new type of boron nitride aerogel can be obtained.
[0057] According to the characteristics of metal smelting, the flue gas composition was simulated. The gas was distributed in nitrogen N2 atmosphere and 82% nitrogen N2 + 12% oxygen O2 + 6% carbon dioxide CO2 atmosphere, with a gas flow rate of 1L / min. Heavy metal salts were added to the front section of the double-temperature tube furnace to simulate the heavy metals in the flue gas. The specific components were Fecl2, Cdcl2 and Pbcl2, and the addition amount was 5g each. Incineration began in the front section of the double-temperature tube furnace, and the incineration temperature was 900±50℃ , place the modified boron nitride aerogel in the second half of the dual-temperature section tubular furnace, set the temperature to 300-600±10℃, open the front section of the tubular furnace first, calculate the time and then open the second half of the tubular furnace, so that the front and back sections reach the set temperature at the same time, and then put the container containing heavy metal salts into the first half of the tubular furnace, and put the boron nitride aerogel adsorbent into the second half, and take samples every 10 minutes at 300-600±10℃ to identify the effects of adsorption time and adsorption temperature on adsorption capacity. The experimental tail gas was treated with 10% nitric acid HNO3 by volume and 5% sodium hydroxide NaOH by mass. After the experiment, the heavy metal content in the boron nitride aerogel adsorbent was measured using ICP. When the adsorption time was 40min, the results of nitrogen N2 atmosphere are shown in Table 1 below.
[0058] Table 1 Adsorption capacity of heavy metals by boron nitride aerogel adsorbent at different temperatures in nitrogen N2 atmosphere (mg / g)
[0059] heavy metal 300℃ 400℃ 500℃ 600℃ Zn 0.121 3.27 52.12 130.67 Cd 0.205 2.37 10.87 12.24 Pb 0.226 3.95 17.23 20.56
[0060] It can be seen from Table 1 that, under nitrogen N2 atmosphere, the adsorption amount of heavy metals increases significantly with the increase of adsorption temperature.
[0061] Embodiment 2;
[0062] The operation steps of this embodiment are the same as those of embodiment 1, except that: the nitrogen N2 atmosphere is changed to N2+12% oxygen O2+6% carbon dioxide CO2 to simulate the smoke composition. After the experiment, ICP is also used to detect the adsorption of heavy metal ions by boron nitride aerogel. The results are shown in Table 2 below.
[0063] Table 2 The adsorption atmosphere is N2+12% oxygen O2+6% carbon dioxide CO2, and the adsorption time is 40 min. The adsorption amount (mg / g) of heavy metals by boron nitride aerogel adsorbent at different temperatures is investigated.
[0064] Table 2 Adsorption capacity of heavy metals by boron nitride aerogel adsorbent under mixed atmosphere (mg / g)
[0065] heavy metal 300℃ 400℃ 500℃ 600℃ Zn 0.171 4.960 61.56 167.7 Cd 0.301 3.045 13.53 13.95 Pb 0.214 4.97 20.22 24.59
[0066] It can be seen from Table 2 that after N2+12% oxygen O2+6% carbon dioxide CO2, the adsorption amount increases with the increase of temperature. Compared with the nitrogen N2 atmosphere, the adsorption amount is significantly improved.
[0067] Embodiment 3;
[0068] The operation steps of this example are the same as those of Example 2, except that: in Example 3, the temperature is fixed at 300°C, and the adsorption amount of boron nitride aerogel is explored by changing the time. After the experiment, ICP is also used to detect the adsorption amount of heavy metal ions by boron nitride aerogel. The results are shown in Table 3 below.
[0069] Table 3 Effect of different adsorption times on the adsorption amount (mg / g) of boron nitride aerogel when the adsorption atmosphere is N2+12% oxygen O2+6% carbon dioxide CO2 and the adsorption temperature is 600°C.
[0070] heavy metal 5min 10min 20min 30min 40min Zn 0.526 14.59 81.53 111.00 164.7 Cd 0.049 0.269 6.251 12.77 13.95 Pb 0.204 1.211 10.98 16.29 24.59
[0071] It can be seen from Table 3 that at the same temperature, the adsorption amount of the boron nitride adsorbent increases with the increase of the adsorption time. The increase of the adsorption time can increase the collection efficiency of the adsorbent for heavy metals.
[0072] Based on the data of the above embodiments, it can be seen that the prepared boron nitride aerogel adsorbent with artificial defect sites can effectively collect heavy metal ions in high-temperature flue gas.
[0073] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. The specification and examples are to be considered exemplary only, and the true scope and spirit of the present invention are indicated by the following claims.
[0074] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. Preparation method of boron nitride aerogel adsorbent for removing heavy metal ions in flue gas based on artificial electron vacancies, It is characterized in that The steps include: Step 1: Weigh melamine C 3 H 6 N 6 , boric acid B 2 O 3 、Zncl 2 , formulated to contain melamine C 3 H 6 N 6 , boric acid B 2 O 3 、Zncl 2 Aqueous solution of Step 2: Add tert-butyl alcohol C to the aqueous solution obtained in step 1 4 H 10 O solution, stir and mix evenly; Step 3: ultrasonically treating the mixed solution obtained in step 2, gradually lowering the temperature to room temperature under an ultrasonic environment, and the mixed solution coagulates into floccules; Step 4: freeze-drying the floccules to obtain a freeze-dried substance; Step 5: calcining the freeze-dried material to obtain the boron nitride aerogel adsorbent.
2. The method for preparing a boron nitride aerogel adsorbent for removing heavy metal ions in flue gas based on artificial electron vacancies according to claim 1, It is characterized in that In step 1, melamine C 3 H 6 N 6 , boric acid B 2 O 3 、Zncl 2 The mass ratio is one of 1:0.5:0.05, 1:0.5:0.25, and 1:0.5:0.
01.
3. The method for preparing a boron nitride aerogel adsorbent for removing heavy metal ions in flue gas based on artificial electron vacancies according to claim 1, It is characterized in that In step 1, a melamine C 3 H 6 N 6 , boric acid B 2 O 3 、Zncl 2 When preparing an aqueous solution, use 105 ml of deionized water at an ambient temperature of 20-30°C and stir with a glass rod until the mixture is evenly mixed. The stirring time is 20±10 minutes.
4. The method for preparing a boron nitride aerogel adsorbent for removing heavy metal ions in flue gas based on artificial electron vacancies according to claim 1, It is characterized in that In step 2, the mixed solution and tert-butyl alcohol C 4 H 10 The volume ratio of O solution is 7:
3.
5. The method for preparing a boron nitride aerogel adsorbent for removing heavy metal ions in flue gas based on artificial electron vacancies according to claim 1, It is characterized in that In step 2, the mixed solution and tert-butyl alcohol C 4 H 10 The O solution was mixed under the conditions that the water bath temperature was set at 85°C and the rotation speed was set at 400 rpm. The ultrasonic time in step 3 was 2 h, and the temperature was reduced from 85°C to room temperature 20-30°C.
6. The method for preparing a boron nitride aerogel adsorbent for removing heavy metal ions in flue gas based on artificial electron vacancies according to claim 1, It is characterized in that The freeze drying time in step 4 is 48h.
7. The method for preparing a boron nitride aerogel adsorbent for removing heavy metal ions in flue gas based on artificial electron vacancies according to claim 1, It is characterized in that The calcination in step 5 is carried out using nitrogen N 2 As a protective atmosphere, the gas flow rate is 50 to 300 ml / min.
8. The method for preparing a boron nitride aerogel adsorbent for removing heavy metal ions in flue gas based on artificial electron vacancies according to claim 1, It is characterized in that In step 5, the calcination time is 3 to 5 hours, and the calcination temperature is 1000 to 1300°C.
9. A use of the boron nitride aerogel adsorbent as claimed in any one of claims 1 to 8, It is characterized in that The adsorbent is used for adsorbing heavy metals and fine particles in high-temperature flue gas.
Citation Information
Cited By
Graded porous guanidyl resin-based CO2 adsorption material and preparation method thereof
CN120001343A
A hierarchical guanidine resin-based CO2 adsorbent material and its preparation method
CN120001343B
